Sheikh Mujib : triumph and tragedy - Karim, S. A. 1928- (Dhaka : The University Press, 2005)
Biography of Sheikh Mujibur Rahman, 1922-1975, former president and nationalist from Bangladesh; includes his political career, 1948-1975.
Includes bibliographical references and index.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Presidents -- Bangladesh -- Biography; Nationalists -- Bangladesh -- Biography; Bangladesh -- Politics and government; Bangladesh -- Politics and government -- 1971-